The Perceptive of Student Teachers Faculty as Millennial Generations Towards Life Skills Through Learning to Design and Practical Implementation - Sahetapy, Meilane (FMIPA UNNES, 2020)
This research aims to recognize the notion from teacher faculty students as millennial generation towards life skills through design lesson and practising implementation. The data was conducted on July 2018, based on academic calendar in 2018/2019. The data was collected from 55 teacher faculty students who were devided into groups that took practice subject and laboratory management courses. The research was a descriptive quantitative research. It was used to collect and to obtain the data which could be quantified with number. The descriptive research is used to describe and to interpret object which are based on the true datas. Meanwhile, the descriptive quantitative research is used to explain existing phenomenon which uses number to illustrate characteristic individually or group. The data collection technique used questioner and descriptive statistic analysis. The general proficiency in the study was about personal skill (thinking skill and self-awareness skill). The research findings about the notion from student teacheras millennial generation through personal skill and social skill were primely 92.72% about proficient thought, good category for self-awareness proficiency at 92.67%, primely category for verbal proficiency at 82.87%, and primely category for cooperative proficiency at 93.72%.